A SOCIOLINGUISTIC ANALYSIS OF INDOGLISH PHENOMENON IN SOUTH JAKARTA - Angelina Diva Wijaya; Barli Bram (IKIP Siliwangi, 2021)
This paper investigated the variety of code-mixing expressions in the Indoglish phenomenon which happens in South Jakarta or Jaksel, for short. Interestingly, Indoglish has become a communication means among teenagers. The researchers chose this topic since it went viral and interesting. This research was conducted to identify the words which are frequently used as Indoglish expressions. The researchers used sociolinguistic analysis as the method of this study. There were 12 tweets from 8 websites to be investigated. The data were then identified and analyzed to explore the Indoglish phenomenon. Results showed there were 78 English words from 12 tweets in eight websites, revealing the four most frequently words as Indoglish expressions. The Indoglish phenomenon was popular among teenagers in the bilingual or mulitilingual society when communicating with their online friends, for example when making jokes and Indoglish was considered prestigious.